البصمة الصوتية لبعض أنواع الجنس Anthocharisوالجنس Euchloe (Lepidoptera: Pieridae) في حلب - كعدة فاضل; زاريكيان نوشيك (Latakia University Journal -Biological Sciences Series, 2014)
أجريت الدراسة في مختبر التنوع الحيوي بكلية العلوم جامعة حلب من الشهر الثالث حتى الشهر التاسع لعام 2012 حول القيمة التصنيفية للبصمة الصوتية عند الأنواع الحيوية وتم تسجيل البصمة الصوتية (طقطقة الأجنحة) لبعض أنواع جنس Anthocharisوالجنس Euchloeمن ذكور وإناث. بينت الدراسة أن البصمة الصوتية لكل نوع تختلف عن البصمة الصوتية للأنواع الأخرى، كما أنها تختلف عند شقي النوع الواحد اختلافاً طفيفاً وهذا ما يتوافق مع نتائج التصنيف الكلاسيكي. إن هذه الدراسة مبنية على الأنواع التي تم جمعها من قبل المؤلفان من مناطق مختلفة من حلب والأنواع والبصمة الصوتية محفوظة في جامعة حلب، كلية العلوم ، قسم الحياة الحيوانية. A study was conducted in the laboratory of biodiversity of Aleppo university’s science faculty department of zoology, from the March to September of 2012. The research was about the taxonomic value of sound-print for some bio species. Thus, have been recorded the sound-print (wing clicks) of some species of Anthocharissp.and Euchloe sp.of males and females. This study revealed, that theacoustic signatureof each speciesdiffers from theother, as the two genders of the same species different slightly and this is whatagreeswiththe results ofthe classicaltaxonomy. This studyis based onthe speciesthat have beencollected bythe authorsfrom different areasin Aleppo. Species and acoustic signaturereservedat Aleppo University, Faculty of Science,Department ofanimal life.